Career counselling and guidance in the workplace : a manual for career development practitioners - Coetzee, Melinde (Juta, 2016)
Career Counselling and Guidance in the Workplace: A manual for career development practitioners gives a comprehensive overview of career counselling and guidance services, practices, tools and techniques for career development practitioners in South Africa. The third edition of this leading textbook has been extensively updated to reflect research and theory in career development theory and intervention that apply to the 21st Century organisational context. Additional real-life case studies that reflect the diverse population groups of South Africa have been added to illustrate how the theory is applied in career counselling practice. This edition further incorporates the role and competencies of career development practitioners as outlined in the new national frameworks. The book has been written for postgraduate students and career development practitioners who specialise in career psychology and counselling. Human resource practitioners, psychologists, psychometrists and registered counsellors who provide career development services to individuals and employers will also benefit from the book.